MODERN APPROACHES TO DIAGNOSING AND DIFFERENTIATING DRUG-RESISTANT TUBERCULOSIS (International journal of medical sciences, 2025)
Drug-resistant tuberculosis (DR-TB), including multidrug-resistant (MDR-TB) and extensively drug-resistant (XDR-TB) forms, is a critical global health challenge. The field of diagnostics is rapidly evolving, moving away from slow, traditional culture methods toward fast, molecular techniques that can identify resistance within hours or days. This review explores the main diagnostic methods for DR-TB, highlighting their strengths, weaknesses, and role in clinical practice. It pays special attention to automated molecular platforms and next-generation sequencing (NGS), assessing their potential for widespread use.